2020
DOI: 10.1039/c9ra10576j
|View full text |Cite
|
Sign up to set email alerts
|

Comparing chemical composition and lignin structure of Miscanthus x giganteus and Miscanthus nagara harvested in autumn and spring and separated into stems and leaves

Abstract: Miscanthus crops possess attractive properties such as high photosynthesis yield and carbon fixation rate. Moreover, M. nagara, shows good frost tolerance. Monolignol ratio and most abundant linkages of the isolated lignins have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 90 publications
2
25
0
6
Order By: Relevance
“…The stem and mixture lignins, for example, have a relatively high share of approximately 20 % or more (peak value for M. sinensis Sin2 with over 30 %). In the leaf-derived lignins, the proportions are significantly lower on average.Results presented here for stem versus leaf-based lignins are in good agreement with previously published studies including further data such as crop yields, chemical composition of the biomasses, ash contents[30,31,43,44] and calorific values[43]. If the highest possible lignin content is desired, stem samples should be chosen, specifically from the M. x giganteus genotype, which revealed lignin contents up to 27 %.From a European agricultural perspective, the genotype M. nagara (NagG10) might be the most suitable for further uses due to its high crop yield and winter hardiness.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The stem and mixture lignins, for example, have a relatively high share of approximately 20 % or more (peak value for M. sinensis Sin2 with over 30 %). In the leaf-derived lignins, the proportions are significantly lower on average.Results presented here for stem versus leaf-based lignins are in good agreement with previously published studies including further data such as crop yields, chemical composition of the biomasses, ash contents[30,31,43,44] and calorific values[43]. If the highest possible lignin content is desired, stem samples should be chosen, specifically from the M. x giganteus genotype, which revealed lignin contents up to 27 %.From a European agricultural perspective, the genotype M. nagara (NagG10) might be the most suitable for further uses due to its high crop yield and winter hardiness.…”
supporting
confidence: 91%
“…In the following, the organosolv process, the determination of the chemical composition according to the NREL procedure as well as the HSQC NMR analyses are described. Further details could be found in the corresponding studies reported by our group [30,31,43,44].…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Besides crop and cell wall composition, focus of current research is also directed toward Miscanthus-derived lignins and their detailed 3D structure, including the monolignol ratio (G, H, S, Figure 1) and corresponding interunit linkages (Figures 2-4) [27][28][29][30][31]. Both the G/H/S ratio and the linkages strongly depend on the biomass origin (crop genotype) and biomass treatment (pulping) method for lignin isolation.…”
Section: Introductionmentioning
confidence: 99%